Development and characterization of novel ZnO-loaded electrospun membranes for periodontal regeneration. Issue 9 (September 2015) - Münchow, Eliseu A.; Albuquerque, Maria Tereza P.; Zero, Bianca; Kamocki, Krzysztof; Piva, Evandro; Gregory, Richard L.; Bottino, Marco C.
Graphical abstract